Proceedings. 26th International Conference on Software Engineering
DOI: 10.1109/icse.2004.1317468
|View full text |Cite
|
Sign up to set email alerts
|

Skoll: distributed continuous quality assurance

Abstract: Quality assurance (QA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 7 publications
1
87
0
Order By: Relevance
“…In our previous efforts [1] we performed these steps manually, making numerous errors. Overall, it took around 48 hours of CPU time to run the ∼50,000 experimental tasks dictated by the experimental design.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous efforts [1] we performed these steps manually, making numerous errors. Overall, it took around 48 hours of CPU time to run the ∼50,000 experimental tasks dictated by the experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…Managing these variable platform aspects effec- In our initial Skoll approach, creating a benchmarking experiment to measure QoS properties required QA engineers to write (1) the header files, source code, that implement the functionality, (2) the configuration and script files that tune the underlying ORB and automate running tests and output generation, and (3) project build files (e.g., makefiles) required to generate the executable code. Our experience during our initial feasibility study [1] revealed how tedious and error-prone this process was since it required multiple manual steps to generate benchmarks, thereby impeding productivity and quality in the QA process.…”
Section: Enhancing Skoll With a Model-based Qos Improvement Processmentioning
confidence: 99%
See 2 more Smart Citations
“…It could contain other sub-components, but such architectural information would not be used in this focus area. In our own research we have started by developing a system and approach currently called QUASI (Quality as a Service Infrastructure) [11,5,6,9]. QUASI's analytical cornerstone is a model of the design space that implicitly captures all configurations on which test jobs might run.…”
Section: Testing Individual Componentsmentioning
confidence: 99%